Pharmacovigilance of quality deviations in the public healthcare system - Carolina Resende Bitencourt (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Drug quality deviation (DQD) is the disagreement with the parameters at the registration with after commercialization step. Pharmacovigilance programs should be notified of DQD to ensure drug efficacy and support patient safety.